Experience with Constructing Code Hunt Contests - Horspool, R. Nigel; Bishop, Judith; Halleux, Jonathan de; Tillmann, Nikolai; Halleux, Jonathan "Peli" de (CHESE 2015 Proceedings of theProc.1st International Workshop on Code Hunt Workshop on Educational Software Engineering (CHESE), 2015)
Puzzles are the basic building block of Code Hunt contests. Creating puzzles and choosing suitable puzzles from the puzzle bank turns out to be a complex operation requiring skill and experience. Constructing a varied and interesting mix of puzzles is based on several factors. The major factor is the difficulty of the puzzle, so that the contest can build up from easier puzzles to more difficult ones. For a successful and fun contest aimed at the expected abilities of the contestants, other factors include the language features needed to solve the puzzle, clues to provide when the puzzle is presented to the player, and test cases to seed into the Code Hunt engine. We describe our experience with contest construction over a period of year and provide guidelines for choosing and making adjustments to the puzzles so that a Code Hunt contest will provide a satisfying trouble-free experience for the contestants.
http://doi.acm.org/10.1145/2792404.2792405